Estimating the embodied energy in ceramic bricks, blocks and tile production materials in the State of Rio Grande do Sul - Manfredini, Constance (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
Although there is much international literature on the environmental impacts of building materials, the number of studies on such impacts in Brazil is relatively small. This constitutes a barrier to determine the environmental impact of local building materials, and, consequently, the impact caused by buildings and the building sector. This article presents the main results of a research project aiming to identify quantitative and qualitative environmental impacts caused by ceramic bricks, blocks and tiles production, in the State Rio Grande do Sul. It is based on data collected in interviews and visits to 20 plants, from a wide range of sizes (producing from 40,000 to 1,500,000 bricks/month), emphasising aspects related to the energy consumption. The data analysis leads to an estimate of the embodied energy of local ceramic materials, and allows a comparison to be made with estimates published in the national and international literature.